Hybrid-driven Disc-shaped Autonomous Underwater Vehicle with High Maneuverability and Gliding Capability: Design and Experiments - Li, Haoda; Jin, Zhihang; Huang, Jin; Liu, Zichen; Peng, Xianyu; Wang, Zhikun; Chen, Ying (IEEE robotics and automation letters, 2025)
This paper presents the mechatronic design and implementation of a hybrid-driven disc-shaped autonomous underwater vehicle (HD-AUV). The hybrid-driven system integrates a buoyancy adjustment system and propeller thrusters, enabling the HD-AUV to achieve both high maneuverability motion and energy-efficient gliding. These capabilities correspond to two distinct motion modes: AUV mode and glider mode. In AUV mode, the HD-AUV leverages the rotational symmetry of its disc-shaped design to achieve four degree-of-freedom (4-DOF) motion control. This configuration, supported by four propeller thrusters, facilitates high-maneuverability actions, including fixed-point hovering and in-place turning. In glider mode, the integration of rotatable dorsal fins and horizontal propeller thrusters enables the HD-AUV to transition seamlessly between diving and ascending phases without the conventional mass-shifting mechanisms used in torpedo-type gliders. Numerical simulations are conducted to evaluate the steady glide performance of the HD-AUV, focusing on lift-to-drag ratios and hydrodynamic coefficients. Comprehensive pool experiments, encompassing multi-DOF maneuvers and gentle gliding, demonstrate the exceptional locomotion capabilities of the HD-AUV and validate the accuracy of the proposed dynamic model. These hybrid motion modes hold significant promise for underwater operations in complex seafloor environments.